Weathering shocks: The effects of weather shocks on farm input use in sub-Saharan Africa - Aimable Nsabimana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
There has been much discussion on climate change and its adverse effects on agriculture, including excessive loss of food production. In regions such as sub-Saharan Africa, where agriculture is the major source of household livelihoods, shocks in weather patterns affect farmers' expectations of farm yield and hence the decision to adopt farm inputs such as fertilizers and pesticides and the extent of their utilization, particularly given the relatively high cost of these inputs. In this study, I explore the relationship between weather shocks and the intensity of inputs use at the plot level using large-scale national panel data from three African countries: Niger, Nigeria, and Tanzania. By combining monthly drought index data with a rich Living Standards Measurement Study-Integrated Surveys on Agriculture dataset, I find that the intensity of chemical fertilizer use reduces much more in drought-prone areas than in less drought-prone areas during growing seasons. I also find that drought during lean seasons is associated with higher pesticide uptake. The evidence suggests that drought induces farmers to purposively reduce farm investments, including yield-enhancing technology such as chemical fertilizer, hence worsening adverse farm yield effects.
Keywords: Q12; Q54; O13; 330; chemical fertilizer; agriculture; climate change; sub-Saharan Africa